how would i complete this problem two different ways?

Where is the problem?

----------------------------------------------------------------

Ok, I'll work on this now.

Here's one way:

(sint + cost)^2 = sin^2t + 2sintcost + cos^2t = 2sintcost + (sin^2t + cos^2t) = 2sintcost + 1

Then,

(2sintcost + 1) / sintcost = 2 + 1/sintcost = 2 + sectcsct

Now I'll work on another way

(sint + cost)^2 / sintcost = (sint+cost)(sint+cost) / sintcost

= (1/cost + 1/sint)(sint + cost)

= (sect + csct)(1/csct + 1/sect)

= sect/csct + sect/sect + csct/csct + csct/sect

= sect/csct + 1 + 1 + csct/sect

= 2 + sec^2t/sectcsct + csc^2t/sectcsct

= 2 + (sec^2t + csc^2t) / sectcsct

= 2 + sectcsct / (cos^2t+sin^2t)

= 2 + sectcsct / 1

= 2 + sectcsct

Thanks!

You're welcome:)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up